Miguel Delibes and the Genius of an Imagined Reality (XXI Century. Spanish Literature and Culture, 2003)
The author explains that the genius of Miguel Delibes’ literature lies on the creation of words in which the reader can drown and feel as their own, built upon realities as daily as those of a frustrated wife who reproaches her husband’s corpse of everything he never did, the wisdom of a child who lives in a cave with his rat-hunter father or that of a hunter on the verge of death, who receives the Anointing of the Sick, believing in the existence of heaven for those of his kind.
Keywords: Miguel Delibes; Novel; Narrative